LYAPUNOV SPECTRA FOR KAPITZA OSCILLATOR - Nayyer Iqbal; Shahid Ahmad; Muhammad Hussain (Journal of the Indonesian Mathematical Society, 2011)
Here we purpose a simple but realistic model of one dimensional nonlinear Kapitza oscillator driven by sin- or cos- rapidly external oscillating periodical force. The model has a parameter 2gl=a22 of dimension one, depending on the amplitude a and frequency of modulation . Changing its value we construct phase portraits of the system in the neighbourhood of fixed points and demonstrate the changing in Lyapunov spectrum. Our purpose is to observe the behavior of system at fixed points due to the different structures of the Lyapunov spectra.DOI : http://dx.doi.org/10.22342/jims.17.1.12.39-48